Full-length transcriptomic analysis in murine and human heart reveals diversity of PGC-1α promoters and isoforms regulated distinctly in myocardial ischemia and obesity - Oehler, Daniel; Spychala, André; Gödecke, Axel; Lang, Alexander; Gerdes, Norbert; Ruas, Jorge; Kelm, Malte; Szendrödi, Julia; Westenfeld, Ralf (BMC biology, 2022)
Peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) acts as a transcriptional coactivator and regulates mitochondrial function. Various isoforms are generated by alternative splicing and differentially regulated promoters. In the heart, total PGC-1α deficiency knockout leads to dilatative cardiomyopathy, but knowledge on the complexity of cardiac isoform expression of PGC-1α remains sparse. Thus, this study aims to generate a reliable dataset on cardiac isoform expression pattern by long-read mRNA sequencing, followed by investigation of differential regulation of PGC-1α isoforms under metabolic and ischemic stress, using high-fat-high-sucrose-diet-induced obesity and a murine model of myocardial infarction.
Gesehen am 19.08.2022